Changes of action strategies in metallurgical enterprises in time of economic crisis - Božena Gajdzik (Metalurgija, 2013)
The topic of the article is the change in action strategy of metallurgical enterprises in time of economic slowdown. The first part of article presents results of literature analyses, opinions of scientists concerning changes in behaviours of enterprises in time of bad conjuncture. In next part of the article the author concentrates on verification of argument concerning the changes in action strategies of enterprises in Polish metallurgical sector. Shown examples of changes are confronted with literature studies presented in the first part of the article.